The Teacher Fosters Students' Courage and Critical Attitude (Lembaga Pengembangan Kinerja Dosen, 2024)
Learners are the main focus in the learning process, which needs to be given space and opportunity to express their abilities in developing their potential and attitude of daring to argue and their critical attitude, but often students are reluctant to give their opinions, therefore this research will be a bridge for teachers to pay more attention and crave students who are less critical in learning activities. To complete this scientific paper, the author uses a literature study method or library research with a descriptive qualitative approach. To realize students who have courage and a good critical attitude, the teacher must be able to create a sense of security for students, be able to be friends, be able to motivate, and be able to create a pleasant learning atmosphere that can attract students' interest in learning.